Rancang Bangun Website Pemesanan Alat Tulis Kantor Dengan Mengimplementasikan Waterfall Pada Toko Bokir Semarang - Azis, Dimas Luthfi; Utomo, Agus Prasetyo (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Toko Bokir Semarang, located on Jalan Lebdosari Raya, West Semarang, provides office and school stationery, as well as photocopying services. Currently, stock management, transaction recording, and payment are still done using conventional methods. This research aims to design and develop a web system for selling office stationery using the CodeIgniter 3 Framework with the Waterfall method. The development process includes requirements analysis, system design, implementation, testing, and maintenance. Data was collected through observations and interviews to understand the workflow. The result of the research is a website with features of product management, ordering, payment, delivery, and reports. With this website, it is expected that the quality of service can improve and the operational efficiency of Toko Bokir Semarang can be well supported.